Martin Sarmiento and Oriental studies: the edition of Casiri’s Bibliotheca Arabica-Hispana - Varela-Orol, Concha (Revista General de Información y Documentación, 2012)
The purpose of this paper is to study the contribution of Martin Sarmiento in the first project carried forward in Spain during the 18th century (Eighteenth Century, Enlightenment) to revive Arabic studies, the catalogue of the Arabic manuscripts of the Escorial by Miguel Casiri. This contribution is analysed in two ways: his assessment to the ideological framework of the project as part of his reflection about the construction of a national memory, constituent element on the creation of the modern state, and his consideration on the operational issues that should be implemented to carry out the work of Casiri.